Valorization of whey proteins and beetroot peels to develop a functional beverage high in proteins and antioxidants - Abdo, Eman M.; Allam, Marwa G.; Gomaa, Mohamed A. E.; Shaltout, Omayma E.; Mansour, Hanem M. M. (Frontiers in Nutrition, 2022)
Adequate protein and antioxidant intake are crucial for everyone, particularly athletes, to promote muscle performance and prevent muscle damage. Whey proteins are high-quality proteins with high digestibility and bioavailability; beetroot peels are rich in bioactive components with potent antioxidant activity. The present study was designated to develop a functional beverage based on mixing whey protein isolate (5%) with different concentrations of beetroot peel water extract (1, 2.5, and 5%) and being flavored with strawberries puree (5%). And examine the stability of the physicochemical parameters and the bioactive components of the beverages during cold storage (4 ͦC) for 14 days. Whey protein isolates enriched the juices with 4.65-4.69% of a stable protein content during the storage. Besides, the extract revealed a concentration-dependent effect on the bioactive components, the antioxidant activity, and the microbial load of the juices; distinguished the fresh juices by their high betalain content in a range of 87.31-106.44 mg/l. Beverages with 2.5% peel extract (T2) possessed the preferable sensory attributes compared to control and other treatments. On day 0, phenolics and flavonoids increased in (T2) by 44 and 31% compared to the control, which elevated the scavenging activity of the juice (T2) (P<0.05). At the end of the storage period (14 days), phenolics and flavonoids of T2 recorded their lowest values, 26.23 and 21.75 mg/ml, respectively. However, they stood higher than phenolics (22.21 mg/ml) (p<0.05) and flavonoids (18.36 mg/ml) (p>0.05) of control. Similarly, betalain degraded by 45% to reach 47.46 mg/l in T2, which reduced the redness (a*) and increased the yellowness (b*) values. Consequently, whey/strawberry/beetroot peel (5:5:2.5 w/v/w) in d.H2O is a functional beverage that provides the body with a high-quality protein and a considerable amount of antioxidants that could improve exercise performance and avoid insufficient protein intake for athletes.